Altered methylation and expression of ER-associated degradation factors in long-term alcohol and constitutive ER stress-induced murine hepatic tumors - Han, Hui; Hu, Jay; Lau, Mo Yin; Feng, Min; Petrovic, Lydia M.; Ji, Cheng (Frontiers in Genetics, 2013)
Mortality from liver cancer in humans is increasingly attributable to heavy or long-term alcohol consumption. The mechanisms by which alcohol exerts its carcinogenic effect are not well understood. In this study, the role of alcohol-induced endoplasmic reticulum (ER) stress response in liver cancer development was investigated using an animal model with a liver knockout of the chaperone BiP and under constitutive hepatic ER stress. Long-term alcohol and high fat diet (HFD) feeding resulted in higher levels of serum alanine aminotransferase (ALT), impaired ER stress response, and higher incidence of liver tumor in older (aged 16 months) knockout females than in either middle-aged (6 months) knockouts or older (aged 16 months) wild type females. In the older knockout females, stronger effects of the alcohol on methylation of CpG islands at promoter regions of genes involved in the ER associated degradation (ERAD) were also detected. Altered expression of ERAD factors including derlin 3, Creld2 (cysteine-rich with EGF-like domains 2), Herpud1 (ubiquitin-like domain member), Wfs1 (wolfram syndrome gene), and Yod1 (deubiquinating enzyme 1) was co-present with decreased proteasome activities, increased estrogen receptor alpha variant (ERa36), and enhanced phosphorylations of ERK1/2 (extracellular signal-regulated protein kinases 1 and 2) and STAT3 (the signal transducers and activators of transcription) in the older knockout female fed alcohol. Our results suggest that long-term alcohol consumption and ageing may promote liver tumorigenesis in females through interfering with DNA methylation and expression of genes involved in the ER associated degradation.